Cointegration of Different ECG Parametres for Various Physical Tasks - Muntianaitė-Dulkinienė, I.; Poškaitis, V.; Vainoras, A.; Jurevičius, J.; Bikulčienė, L.; Navickas, Z. (Elektronika ir Elektrotechnika, 2009)
Any physical load evokes systemic reaction of organism functions combining cardiovascular system, central nervous system and muscles. ECG parameters, their variations and mechanism of action/functioning reflect the peculiarities of the activity of these systems. The algebraic method of data cointegration, applied to the current work, allows observing the ways of chosen parameter concatenation during various physical tasks. The calculation of the concatenation of the parameters by applying the analysis method of second order matrices better reveals the inner processes and changes of the organism than the calculation based on the correlation of the given parameters. Each analysed concatenation of parameters was observed due to its dynamics, which depends upon the stage of the study and the physical task. Ill. 4, bibl. 5 (in English; abstracts in English, Russian and Lithuanian).